2022
DOI: 10.3390/ijms23126859
|View full text |Cite
|
Sign up to set email alerts
|

AB186 Inhibits Migration of Triple-Negative Breast Cancer Cells and Interacts with α-Tubulin

Abstract: Breast cancer is one of the leading causes of cancer-related death among females worldwide. A major challenge is to develop innovative therapy in order to treat breast cancer subtypes resistant to current treatment. In the present study, we examined the effects of two Troglitazone derivatives Δ2-TGZ and AB186. Previous studies showed that both compounds induce apoptosis, nevertheless AB186 was a more potent agent. The kinetic of cellular events was investigated by real-time cell analysis system (RTCA) in MCF-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, AB 186 has been shown to promote microtubule stabilization via direct binding to β-tubulin. AB 186 was also shown to affect an unorganized actin network in MDA-MB-231 cells [62]. Troglitazone itself was also shown to inhibit the migration of highly metastatic PK-1 (pancreatic) and ES-2 (ovarian) cancer cells via inhibition of actin polymerization, lamellipodia formation, and inducing a decrease in the number of actin stress fibers [63,64].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, AB 186 has been shown to promote microtubule stabilization via direct binding to β-tubulin. AB 186 was also shown to affect an unorganized actin network in MDA-MB-231 cells [62]. Troglitazone itself was also shown to inhibit the migration of highly metastatic PK-1 (pancreatic) and ES-2 (ovarian) cancer cells via inhibition of actin polymerization, lamellipodia formation, and inducing a decrease in the number of actin stress fibers [63,64].…”
Section: Discussionmentioning
confidence: 98%
“…However, very few studies have investigated the effect of microtubule-targeting drugs on the integrity of the actin cytoskeleton in cancer cells. For example, AB 186, a troglitazone derivative and microtubule-stabilizing compound, inhibits the migration of the two highly metastatic TNBC cell lines, MDA-MB-231 and Hs578T [62]. In addition, AB 186 has been shown to promote microtubule stabilization via direct binding to β-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…5-Benzylidenethiazolidine-2,4-dione (BTZD) 1 is a privileged scaffold present in a wide range of bioactive molecules including antidiabetics, antivirals, anti-inflammatories, or antiproliferative compounds (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the readers of this Special Issue will learn about the anti-tumor activity of neosynthesized, natural, and already-available drugs that could be used as new anti-BC drugs. Indeed, the contributing authors have reported the antiproliferative activity of berberine and troglitazone derivatives, resveratrol analogs, atoquavone, clotrimazole, fenticonazole, compounds specifically targeting mitochondrial activity, and valproic acid, as well as NAMPT and carbonic anhydrase IX inhibitors [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
mentioning
confidence: 99%